2020
DOI: 10.1186/s12864-019-6428-0
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis between constructed SNPLDBs and GCA effects of 9 quality-related traits in parents of hybrid rice (Oryza sativa L.)

Abstract: Background: The general combining ability (GCA) of parents in hybrid rice affects not only heterotic level of grain yield and other important agronomic traits, but also performance of grain quality traits of F 2 bulk population which is the commodity consumed by humans. In order to make GCA improvement for quality traits in parents of hybrid rice by molecular marker assisted selection feasible, genome-wide GCA loci for quality traits in parents were detected through association analysis between the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Thus these hybrid combinations could be utilized for improving heterosis and achieving a highyielding genotype. The results demonstrated that no specific combination had positive SCA effects for all characters concurrently; this is consistent with those reported from previous results [24][25][26][27][28]. Our finding demonstrated that a certain cross-combination with a high positive SCA for different characters had both parents with a better GCA.…”
Section: Mean Performance and Combining Abilitysupporting
confidence: 92%
See 1 more Smart Citation
“…Thus these hybrid combinations could be utilized for improving heterosis and achieving a highyielding genotype. The results demonstrated that no specific combination had positive SCA effects for all characters concurrently; this is consistent with those reported from previous results [24][25][26][27][28]. Our finding demonstrated that a certain cross-combination with a high positive SCA for different characters had both parents with a better GCA.…”
Section: Mean Performance and Combining Abilitysupporting
confidence: 92%
“…In addition, it is a powerful tool to clarify the nature of gene action for desired characters [25]. It was reported that the GCA has a vital role in the heterotic degree of grain yield and its component characteristics [26]. Our current study observed that all parental lines were identified as the best combiner for at least one of the studied traits and a good combiner for a minimum two yield characteristics (Table 3).…”
Section: Mean Performance and Combining Abilitysupporting
confidence: 52%
“…This suggested that some genes or loci differ as to per se performances and/or corresponding GCA effects for these traits. Previous study also revealed the different genetic basis between per se performances and corresponding GCA effects for the traits (Eltahawy et al, 2020). Due to heterotic effects, differences between individuals in the testcross population were significantly reduced.…”
Section: Potential Utilization Of Main Qtl For Gca Effects In Maize Hmentioning
confidence: 90%
“…qKT1-2 and qHKW5-1 explained only 5.72 and 5.12% of the observed variation for GCA effects of KT and HKW individually. Previous studies suggested that traits GCA effects were mainly related with poly-genes rather than with major gene controlling the per se performances for the traits (Basava et al, 2019;Eltahawy et al, 2020), further loci associated with GCA effects should be explored in maize.…”
Section: Potential Utilization Of Main Qtl For Gca Effects In Maize Hmentioning
confidence: 99%
“…The parents, 'WTSC9059' , 'Sakha101' , 'Sakha102' and 'Sakha108' were recognized as good general combiners due to their maximum positive GCA effect values for most traits and could be utilized in breeding program to enhance grain yield and its related traits. Eltahawy et al (2020)but also performance of grain quality traits of F2 bulk population which is the commodity consumed by humans. In order to make GCA improvement for quality traits in parents of hybrid rice by molecular marker assisted selection feasible, genome-wide GCA loci for quality traits in parents were detected through associa-tion analysis between the effects of GCA and constructed single nucleotide polymorphism linkage disequilibrium blocks (SNPLDBs reported the general combining ability (GCA) of parents in hybrid rice affects playing vital role in both heterotic level of grain yield and other important agronomic traits.…”
Section: Specific Combining Ability (Sca) Ef-fectsmentioning
confidence: 99%